Evidence on key policies for African agricultural growth - Diao, Xinshen; Kennedy, Adam; Badiane, Ousmane; Cossar, Frances; Dorosh, Paul A.; Ecker, Olivier; Ghebru, Hosaena H.; Headey, Derek D.; Mabiso, Athur; Makombe, Tsitsi; Malek, Mehrab; Schmidt, Emily (International Food Policy Research Institute, 2013)
The paper examines policies to encourage the adoption of agricultural inputs, initiate greater private-sector investment in agriculture and agro-industries, and manage price volatility while encouraging openness. The paper further reviews successful land tenure policies and property rights systems, reviews the evidence on the synergies between agriculture and nutrition, and examines how CAADP is laying the institutional architecture for improved policy formulation in Africa. In general, the paper finds that although substantial progress has been made, there is considerable scope for improvement.